Electric field influence on the helical structure of peptides: insights from DFT/PCM computations. Issue 29 (12th July 2019) - Ilieva, Sonia; Cheshmedzhieva, Diana; Dudev, Todor
Abstract : The switching of the electric field with a particular directionality could be used for the healing of misfolded proteins. Abstract : The secondary structure of proteins is of prime importance to their proper functioning and protein misfolding may cause serious disorders in the human body. Here, the electric field influence on the conformational stability of model alpha helical peptides is studied by employing density functional theory calculations combined with continuum dielectric method computations. Our results show that the basic parameters of the electric field – its strength and directionality – are determinative for the alpha helix stability. An electric field strength of 0.005 a.u. (2.5 V nm −1 ) applied along the X coordinate axis (the long axis of the helix) in the direction of the μ x component of the molecular dipole moment does affect the peptide conformation, destroys the helix, and leads to the formation of a cyclic-peptide-like structure. Interestingly, the process of denaturation can be reversible when the electric field is switched-off. The reversibility of the process of the electric field induced disruption of the peptide secondary structure suggests a possible mechanism for the healing of misfolded proteins.